Fostering Collaborative Leadership Through Islamic Values: A Strategic Framework - Hussain Othman; Anis Malik Thoha; Muhammad Sahrin bin Haji Masri; Nurefnazahani binti Haji Durani; Mohammad Hilmy Baihaqy Bin Haji Awang Yussof; Noorhizrah binti Mohammad; Sadia Deep (Penerbit USIM, 2024)
E-Proceedings of 7th International Seminar on Philosophy, Civilisations, Ethics, and Islamic Turath (I-STET) 2024 “Sustaining Islamic Heritage, Upholding Philosophy, Spearheading Civilisations and Immersing in Culture” / editor: Ros Aiza Mohd Mokhtar, Farah Laili Muda @ Ismail, Latifah Abdul Latiff, Nuruliza Roslan 15 – 16 Oktober 2024 ( Hibrid) Anjuran :Pusat Pengajian Teras & Institut Sains Islam (USIM) Dengan Kerjasama : Universiti Islam Sultan Sharif Ali, Universiti Islam Selangor, Persatuan Sejarah Malaysia, dan Yayasan PEACE